Mitochondrial dynamics, Leydig cell function, and age‐related testosterone deficiency. Issue 12 (9th November 2022) - Garza, Samuel; Chen, Liting; Galano, Melanie; Cheung, Garett; Sottas, Chantal; Li, Lu; Li, Yuchang; Zirkin, Barry R.; Papadopoulos, Vassilios
Abstract: The mitochondrial translocator protein (18 kDa; TSPO) is a high‐affinity cholesterol‐binding protein that is an integral component of the cholesterol trafficking scaffold responsible for determining the rate of cholesterol import into the mitochondria for steroid biosynthesis. Previous studies have shown that TSPO declines in aging Leydig cells (LCs) and that its decline is associated with depressed circulating testosterone levels in aging rats. However, TSPO's role in the mechanistic decline in LC function is not fully understood. To address the role of TSPO depletion in LC function, we first examined mitochondrial quality in Tspo knockout mouse tumor MA‐10 nG1 LCs compared to wild‐type MA‐10 cells. Tspo deletion caused a disruption in mitochondrial function and membrane dynamics. Increasing mitochondrial fusion via treatment with the mitochondrial fusion promoter M1 or by optic atrophy 1 (OPA1) overexpression resulted in the restoration of mitochondrial function and mitochondrial morphology as well as in steroid formation in TSPO‐depleted nG1 LCs. LCs isolated from aged rats form less testosterone than LCs isolated from young rats. Treatment of aging LCs with M1 improved mitochondrial function and increased androgen formation, suggesting that aging LC dysfunction may stem from compromised mitochondrial dynamics caused by the age‐dependent LC TSPO decline. These results, taken together, suggest that maintaining or enhancing mitochondrial fusion may provide therapeutic strategies to maintain or restore testosterone levels with aging.